2008
DOI: 10.1016/j.freeradbiomed.2008.04.037
|View full text |Cite
|
Sign up to set email alerts
|

γ-Tocopherol nebulization by a lipid aerosolization device improves pulmonary function in sheep with burn and smoke inhalation injury

Abstract: Fire accident victims, who sustain both thermal injury to skin and smoke inhalation, have gross evidence of systemic and pulmonary oxidant damage and acute lung injury. We hypothesized that gamma-Tocopherol (gT), a reactive O 2 and N 2 scavenger, when delivered into the airway will attenuate lung injury induced by burn and smoke inhalation. Acute lung injury was induced in chronically prepared, anesthetized sheep by 40% total burn surface area, 3rd degree skin burn and smoke insufflation (48 breaths of cotton … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 65 publications
1
39
0
Order By: Relevance
“…GraphPad Prism was used for statistical analysis (18). After obtaining normality for all measurements using the Kolmogorov-Smirnov test for goodness-of-fit to normal distribution, a two-way ANOVA for repeated measurements with group and time as factors was applied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GraphPad Prism was used for statistical analysis (18). After obtaining normality for all measurements using the Kolmogorov-Smirnov test for goodness-of-fit to normal distribution, a two-way ANOVA for repeated measurements with group and time as factors was applied.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 5 million microspheres with a diameter of 15.0 Ϯ 0.1 m were injected into the left atrium at BL (preinjury), 3,6,12,18, and 24 h, while reference blood was withdrawn from the femoral arterial catheter at a constant rate of 10 ml/min. The lower part of the trachea just above the carina (to which blood is supplied only by the bronchial artery) was harvested to quantify tracheal blood flow (37).…”
Section: Measurement Of Tracheal Blood Flowmentioning
confidence: 99%
“…In another study, g-tocopherol supplementation reduced antigen induction of rat lung inflammation that was primarily neutrophils (26). It is also reported that nebulized g-tocopherol reduces neutrophilia in burn and smoke inhalation injury in sheep (27). Therefore, g-tocopherol may be of benefit for acute neutrophilic inflammation.…”
mentioning
confidence: 92%
“…[16][17][18] An important chemical property of Vitamin E is its antioxidant activity, and its ability to neutralise peroxides and free oxygen radicals. 19 It is reported that Vitamin E has more powerful antioxidant capacity to prevent lipid peroxidation in the cells than other self-antioxidation systems (Vitamin C, glutathione peroxidase and beta carotene). 6,7,20 Although there is no report concerning the protective effects of Vitamin E against oxidative injury in humans, cardioselective analogs of alpha-tochopherol are used successfully in ischemic rat heart, where it reduced the infarct area and the enzymatic markers.…”
Section: Discussionmentioning
confidence: 99%